Informing road traffic intervention choices in South Africa: the role of economic evaluations - Wesson, Hadley K.H. (Glob Health Action, 2016)
INTRODUCTION: Given the burden of road traffic injuries (RTIs) in South Africa, economic evaluations of prevention interventions are necessary for informing and prioritising public health planning and policy with regard to road safety. METHODS: In view of the dearth of RTI cost analysis, and in order to understand the extent to which RTI-related costs in South Africa compare with those in other low- and middle-income countries (LMICs), we reviewed published economic evaluations of RTI-related prevention in LMICs. RESULTS: Thirteen articles were identified, including cost-of-illness and cost-effectiveness studies. Although RTI-related risk factors in South Africa are well described, costing studies are limited. There is minimal information, most of which is not recent, with nothing at all on societal costs. Cost-effective interventions for RTIs in LMICs include bicycle and motorcycle helmet enforcement, traffic enforcement, and the construction of speed bumps. DISCUSSION: Policy recommendations from studies conducted in LMICs suggest a number of cost-effective interventions for consideration in South Africa. They include speed bumps for pedestrian safety, strategically positioned speed cameras, traffic enforcement such as the monitoring of seatbelt use, and breathalyzer interventions. However, interventions introduced in South Africa will need to be based either on South African cost-effectiveness data or on findings adapted from similar middle-income country settings.